2021
DOI: 10.1038/s41598-021-93576-z
|View full text |Cite
|
Sign up to set email alerts
|

Liquid state properties and solidification features of the pseudo binary BaS-La2S3

Abstract: The high temperature thermodynamic properties of chalcogenides materials based on BaS remain elusive. Herein the pseudo binary BaS-La2S3 is investigated above 1573 K. The liquid properties of BaS-La2S3 are measured by means of high resolution in-situ visualization coupled with thermal arrest measurements in a thermal imaging furnace. This enables to report the first observation of such melts in a container-less setting. The melting points of BaS and La2S3 are revisited at 2454 K and 2004 K respectively. La2S3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In previous work, Stinn et al [35] demonstrated the high solubility of copper sulfide (Cu 2 S) in barium sulfide (BaS). A mixture of BaS and lanthanum sulfide (La 2 S 3 ) was used as the supporting electrolyte in this investigation (binary system characterized by Boury and Allanore [36]). Sokhanvaran et al [32] show that this supporting electrolyte supports ionic transport, while the decomposition voltage of BaS and La 2 S 3 are sufficiently high.…”
Section: Electrolyte Synthesis: Chalcopyritementioning
confidence: 99%
“…In previous work, Stinn et al [35] demonstrated the high solubility of copper sulfide (Cu 2 S) in barium sulfide (BaS). A mixture of BaS and lanthanum sulfide (La 2 S 3 ) was used as the supporting electrolyte in this investigation (binary system characterized by Boury and Allanore [36]). Sokhanvaran et al [32] show that this supporting electrolyte supports ionic transport, while the decomposition voltage of BaS and La 2 S 3 are sufficiently high.…”
Section: Electrolyte Synthesis: Chalcopyritementioning
confidence: 99%